Game criticality in male youth football: Situational and age-related effects on the goal-scoring period in Portuguese national championships - Carlos Humberto Almeida; Paulo Cruz; Ricardo Gonçalves; Rui Batalau; Paulo Paixão; José António Jorge; Pedro Vargas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Research crossing the effects of situational variables with the temporal analysis of goals scored in football is scarce, particularly in youth football. Hence, the present study aimed to (1) analyse the effects of match location, match status, team quality, goal criticality, and age group on match periods in which goals are scored in male youth football, and (2) examine whether the age group (U17, U19, and U23) influences the emergence of critical moments in matches from the Portuguese national championships. The sample consisted of 2,591 goals scored in the U17, U19, and U23 Portuguese national championships during the 2019/2020 season. Chi-square tests revealed that match location, match status, goal criticality, and age group were significantly associated with the goal-scoring period. During the first halves, more goals were scored (1) when playing at home, (2) when teams were tied or losing by one goal (critical circumstances) and (3) by U17 teams. A multinomial logistic regression model revealed that the chances of scoring in the sixth period (vs the first) significantly decreased when playing at home, and in U17 and U19 matches. The U23 teams were more likely to score in the last period regardless of goal criticality. However, the interaction effect of team quality x age group suggests that U17 and U19 teams are more prone to score in later match periods when team ability is equated. These findings enable coaches to improve the tactical, physical, and psychological preparation for competitive youth matches depending on the target age group.